Evaluation of the relationship between the anterior component of occlusal force and postretention crowding - ACAR, ZEYNEP AHÜ (MOSBY, INC, 2002)
The aim of this study was to investigate whether a relationship exists between the anterior component of occlusal force (ACF) and postretention crowding in the mandibular incisor area. The study group comprised 32 adults who had undergone fixed orthodontic treatment in the department clinic at Marmara University in Istanbul, Turkey. In 13 subjects, the mandibular arch was treated without extractions; in 19, it was treated with bilateral first premolar extractions. The average postretention period was 3.5 years. The ACF created in the left side of the mandibular dentition was determined by measuring interdental frictional forces at each contact point mesial to the first molar and distal to the canine. Anatomic contact point displacements between the left mandibular anterior teeth (lateral incisor-canine, central incisor-lateral incisor, and central incisor-central incisor) were measured on plaster casts and summed to provide the irregularity index for these teeth. Correlation analysis was used to assess the relationship between the ACF values at each contact and the irregularity index. In the nonextraction group, statistically significant positive correlations were observed between the ACF and the irregularity index at the 3 contact points that were measured. The strongest correlation was found at the canine-first premolar contact (r = 0.65). In the extraction group, a positive correlation was found between the ACF and the irregularity index (r = 0.49, P <.05) at the second premolar-first molar contact, but no correlation was found at the canine-second premolar contact.